P568 The impact of a virtual clinic on clinical decision-making and healthcare resource use vs. standard care: The Oxford experience. (16th January 2018) - FitzPatrick, M; Ambrose, T; Thomas, L; Cullen, S; Blackburn, G; Davies, K; Travis, S; Keshav, S; Walsh, A; Palmer, R; Cripps, S; Brain, O
Abstract: Background: Optimisation of infliximab (IFX) therapy using proactive therapeutic drug monitoring (TDM) in inflammatory bowel disease (IBD) may reduce drug costs and improve clinical outcomes. 1, 2 The Oxford Virtual Clinic (VC) for biological therapy TDM was started in March 2016. Levels are monitored with each infusion and therapy optimised if clinically appropriate. Aims: To analyse the impact of the VC on clinical decision-making and healthcare resource use compared with ad hoc dose adjustment and TDM (standard care). Methods: Patients commencing IFX therapy for IBD were retrospectively identified from our biologics' database comprising 177 current and 278 previous users of infliximab. Two cohorts were analysed: October 2014–May 2015 (pre-VC) and March–October 2016 (post-VC). All patients were followed up for 12 months. Data were extracted for baseline demographics, details of IFX therapy including changes to therapy, use of TDM, hospital attendance, and endoscopy. Results: Twenty-five and 36 patients met the criteria in the pre-VC and post-VC cohort, respectively. There were no statistically significant differences in cohort demographics or disease characteristics (Table 1). Twenty-two patients were discussed a total of 30 times in the VC. Overall, more patients had adjustments in therapy post-VC (18 of 36 vs. 4 of 25 p = 0.0076) including a switch to alternative biologic (5 of 36), dose adjustment (13 of 36), or introduction of an immunomodulator (4 of 36). There were no differences in total annual biologics cost or average dose per patient between cohorts. Within the post-VC cohort, median IFX trough levels increased ( p = ns) with a reduction in the number of subtherapeutic levels across the period of study. Number of infusion visits, endoscopic procedures, the IBD nurse advice line, or IBD-related admissions did not alter between groups. The mean number of gastroenterology outpatient appointments per patient was lower in the post-VC group (4.28 vs. 5.36, p = 0.0258). Conclusions: The VC has improved clinical decision making by tailoring IFX therapy on a patient-by-patient basis. Those with low-levels are dose optimised or switched early to alternative therapy if appropriate without an increase in overall biologic drug costs. We did not identify any increase in healthcare resource use and there may be a reduction in outpatient appointments. Further biological and clinical outcomes of the VC are being investigated. References: 1. Papamichael K, Chachu K, Vajravelu R, Vaughn B, Ni J, Osternam M et al. Improved long-term outcomes of patients with inflammatory bowel disease receiving proactive compared with reactive monitoring of serum concentrations of infliximab. Clin Gastroenterol Hepatol, 2017;15:1580–1588. 2. Vande Casteele N, Ferrante M, Van Assche G, Ballet V, Compernolle G, Van Steen K et al. Trough concentrations of infliximab guide dosing for patients with inflammatory bowel disease. Gastroenterology, 2015;148: 1320–1329.